ICTs, data and vulnerable people: a guide for citizens - Alexandra Castańeda; Andreas Matheus; Andrzej Klimczuk; Anna Berti Suman; Annelies Duerinckx; Christoforos Pavlakis; Corelia Baibarac-Duignan; Elisabetta Broglio; Federico Caruso; Gefion Thuermer; Helen Feord; Janice Asine; et al. (University of the Basque Country (UPV/EHU), 2021)
ICTs, personal data, digital rights, the GDPR, data privacy, online security… these terms, and the concepts behind them, are increasingly common in our lives. Some of us may be familiar with them, but others are less aware of the growing role of ICTs and data in our lives - and the potential risks this creates. These risks are even more pronounced for vulnerable groups in society. People can be vulnerable in different, often overlapping, ways, which place them at a disadvantage to the majority of citizens; Table 3 in this guide presents some of the many forms and causes of vulnerability. As a result, vulnerable people need greater support to navigate the digital world, and to ensure that they are able to exercise their rights. This guide explains where such support can be found, and also answers the following questions: - What are the main ethical and legal issues around ICTs for vulnerable citizens? - Who is vulnerable in Europe? - How do issues around ICTs affect vulnerable people in particular? This guide is a resource for members of vulnerable groups, people who work with vulnerable groups, and citizens more broadly. It is also useful for data controllers1 who collect data about vulnerable citizens. While focused on citizens in Europe, it may be of interest to people in other parts of the world. It forms part of the Citizens' Information Pack produced by the PANELFIT project, and is available in English, French, German, Italian and Spanish. You are welcome to translate this guide into other languages. Please send us a link to online versions in other languages, so that we can add them to the project website.
Keywords: C89; Z19; D89; 330; General Data Protection Regulation (GDPR); ICTs; citizen science; data management; legal and ethical issues; vulnerability